2018
DOI: 10.1097/prs.0000000000004572
|View full text |Cite
|
Sign up to set email alerts
|

Improving Safety after Abdominoplasty: A Retrospective Review of 1128 Cases

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 22 publications
3
18
0
4
Order By: Relevance
“…Previous studies highlighted various risk factors for complications in abdominoplasty, i.e., age, obesity, smoking, weight loss, and blood loss [10,17]. In our study, smoking habit and body weight at the time of abdominoplasty, but not weight loss since bariatric surgery, were independently associated with increased odds of perioperative complications following abdominoplasty.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies highlighted various risk factors for complications in abdominoplasty, i.e., age, obesity, smoking, weight loss, and blood loss [10,17]. In our study, smoking habit and body weight at the time of abdominoplasty, but not weight loss since bariatric surgery, were independently associated with increased odds of perioperative complications following abdominoplasty.…”
Section: Discussionsupporting
confidence: 54%
“…Although the “fleur-de-lis” is a well-established technique with equivalent complication rates reported in some centers, 64 other authors find the complication rates to be higher. 49 , 54 , 65 It is the author’s opinion that in many cases the aesthetics are better ( Figures 2 and 3 ) without the vertical midline scar, even if some minor side-to-side laxity remains. One center concurs with this assessment and has largely ceased the performance of the “fleur-de-lis” due to concerns regarding the aesthetics of the “hard to disguise” vertical scar as well as, in their experience, a higher complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…Also in this current study, the other baseline risk factors of diabetes, smoking, age, as well as elevated BMI were important, independent and statistically significant contributors to increased complications ( Table 5 ). Along these lines, Dutot et al, 49 in a recent large long-term study, concluded that the other risk factors of age, obesity, and smoking were more important factors than a history of weight loss. The evidence in this current paper as well as the just cited evidence in the literature raises the possibility that although a history of bariatric MWL may present independent risk, there is a collinearity of risk factors that may contribute substantially to the increased complication rates, and these additional comorbidities should be included in the risk calculus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 12 , 22 , 43 One recent study reported 64 hematomas among 1128 anticoagulated abdominoplasty patients (5.7%). 43 Hematomas should not be considered an acceptable trade for a VTE, particularly if a VTE can be identified early in its development, when it is not dangerous, and managed with minimal disruption to the patient's activities and recovery. 10 , 19 Hematomas are distressing to patients and surgeons.…”
mentioning
confidence: 99%